Effects of Chlorinated Polypropylene on the Conformation of Polypropylene in Polypropylene/Chlorinated Polypropylene/Polyaniline Composites. (3rd August 2015) - Chen, Jianjun; Jia, Yueyue; Zhang, Zhiye; Wang, Xinlong; Yang, Lin
Abstract : We investigated the changes in the conformation and crystalline structure of polypropylene (PP) using a combination of Fourier transform infrared spectroscopy (FTIR), wide-angle X-ray diffraction (WAXD), and differential scanning calorimetry (DSC) based on PP/chlorinated PP (CPP)/polyaniline (PANI) composites. The DSC heating thermograms and WAXD patterns of the PP/CPP/PANI composites showed that the β -crystal was affected greatly by the CPP content. Characterization of the specific regularity in the infrared band variation showed that the conformational orders of the helical sequences in PP exhibited major changes that depended on the CPP content. Initially, the intensity ratio ofA 840 / A 810 increased with the CPP concentration and reached its maximum level when the CPP content was <13.22% before decreasing as the CPP content increased further. The effect of increased temperature on the conformation of PP was studied by in situ FTIR. Initially, the intensity ratio ofA 999 / A 973 decreased slowly with increasing the temperature up to 105°C before decreasing sharply with further increases in temperature and then decreasing slowly again when the temperature was higher than 128°C.